THE DEVELOPMENT OF AGRICULTURAL ACTIVITIES IN THE HILL AREA OF DROBOT FOR VALLEY FROM BACĂU DISTRICT, ROMANIA - Bran, Mariana; Dobre, Iuliana; Voicu, Radu (Economics of Agriculture, 2018)
Because of risk hereupon are insecure the natural resources and other environmental elements, must to act in the sustainable development sense. Permanently, are decisive to assure the healthy life conditions (pure water, fresh air, health food). Thus, in studied zone, are imperative field work of an affected areas from natural disaster (inundations, deforestations, and landfall) and friendly technologies based agricultural activities (in crops and animal husbandry).